2000
DOI: 10.1001/archpsyc.57.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Structural Abnormalities of Subicular Dendrites in Subjects With Schizophrenia and Mood Disorders

Abstract: Background: Postmortem studies of the subiculum from subjects with schizophrenia have detected smaller pyramidal cell bodies and diminished immunoreactivity for the dendritic protein, microtubule-associated protein 2. While these findings suggest that subicular pyramidal cell dendrites may be structurally altered in subjects with schizophrenia, this possibility had not been tested directly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
194
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(214 citation statements)
references
References 46 publications
18
194
1
1
Order By: Relevance
“…They could open up new prospects for modeling the pathophysiology of schizophrenia. Not only have SUB anomalies reminiscent of neurodevelopmental failures been described in schizophrenia (Arnold et al, 1995;Arnold, 2000;Rosoklija et al, 2000;Law et al, 2004), but also a reduction in latent inhibition has been reported in neuroleptic-naive patients with schizophrenia (Baruch et al, 1988;Gray et al, 1992Gray et al, , 1995Lubow et al, 2000Rascle et al, 2001. Moreover, the dorsomedial shell part of the nucleus accumbens seems to be the target structure for the common action of neuroleptics (Deutch and Cameron, 1992;Robertson and Fibiger, 1992;Jennings et al, 2006), this being consistent with enhanced dopaminergic transmission in the dorsomedial shell in acute patients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…They could open up new prospects for modeling the pathophysiology of schizophrenia. Not only have SUB anomalies reminiscent of neurodevelopmental failures been described in schizophrenia (Arnold et al, 1995;Arnold, 2000;Rosoklija et al, 2000;Law et al, 2004), but also a reduction in latent inhibition has been reported in neuroleptic-naive patients with schizophrenia (Baruch et al, 1988;Gray et al, 1992Gray et al, , 1995Lubow et al, 2000Rascle et al, 2001. Moreover, the dorsomedial shell part of the nucleus accumbens seems to be the target structure for the common action of neuroleptics (Deutch and Cameron, 1992;Robertson and Fibiger, 1992;Jennings et al, 2006), this being consistent with enhanced dopaminergic transmission in the dorsomedial shell in acute patients.…”
Section: Discussionmentioning
confidence: 88%
“…According to several recent proposals, the psychic disintegration characteristic of this disease would result from a defective connectivity between various integrative regions having a neurodevelopmental origin (Weinberger and Lipska, 1995;Bullmore et al, 1997;Friston, 1998;Lewis and Levitt, 2002;Sawa and Snyder, 2002;Arnold et al, 2005;Foucher et al, 2005). Thus, the ventral subiculum of the hippocampus (SUB) seems to be subjected to neurodevelopmental abnormalities in schizophrenia, as suggested by the cytoarchitectural and cortical morphometric aberrations reported by several authors, particularly in the left hemisphere (Arnold et al, 1995;Arnold, 2000;Rosoklija et al, 2000;Law et al, 2004). Data obtained over the past three decades also support the hypothesis of a functional dysregulation of the mesostriatal dopaminergic neurons in schizophrenia (Swerdlow and Koob, 1987;Harrison, 1999;Carlsson et al, 2001), consistent with a cortico-subcortical disconnectivity (Kegeles et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cytoarchitectural studies have found evidence for an increase in neuronal density, 9 decrease in neuronal size, 10,11 reduced pyramidal neuron dendritic field 12,13 and decreased dendritic spine density 14,15 with similar reductions in neuronal size observed in BPD. 16 Efforts to determine the neurochemical and molecular basis for these cellular alterations have revealed abnormalities in neurotransmission, signal transduction, inhibitory interneuron function and glial cells.…”
Section: Introductionmentioning
confidence: 92%
“…In the terminal fields of entorhinal cortex projections, SNAP-25 expression was decreased 85 . In the hippocampus it was shown that neuron populations had fewer dendritic spines and reduced dendritic arborizations 86 . This observation was supported by studies detecting molecular markers like microtubule-associated protein 2 (MAP2) and spinophilin 87,88 .…”
Section: Schizophrenia As a Disorder Of Disturbed Synaptic Plasticitymentioning
confidence: 99%